Implementasi E-Office Dalam Peningkatan Pengelolaan Tata Naskah Dinas Di Sekretariat Kota Administrasi Jakarta Pusat Tahun 2022 - Wahyudin, Wahyudin (Jurnal Syntax Fusion, 2023)
According to the United Nations e-Government Development Index (EGDI) survey results for 2020, Indonesia was ranked 7th in Southeast Asia and 88th in the world. Indonesia must continue to work towards closing the gap in e-government implementation through Electronic-Based Governance System (SBPE) policy at the central and regional government levels. The government of DKI Jakarta province has taken steps to implement the Electronic-Based Governance System (SBPE) through Government-to-Government (G2G) services by implementing the Governor of DKI Jakarta regulation number 99 of 2021 concerning Official Administrative Management within the DKI Jakarta Provincial Government. The policy is implemented through an information technology-based application called e-office. This research aims to identify, analyze, and understand the obstacles and the efforts made to implement the e-office for improving administrative management at the Secretariat OF Central Jakarta City Administration. The research utilized a qualitative-descriptive method, where the results were presented based on the analysis of interview responses, document observations, and studies conducted. The research employed the theory proposed George C. Edwards III (Pramono, Joko, 2020:17), which encompasses communication, resources, disposition, and bureaucratic structure as crucial aspects. The research results indicated that the implementation of the e-office for improving administrative management at the Secretariat of Central Jakarta City Administration in 2022 has generally been successful.